Kajian Hidrolika Aliran Bangunan Pelimpah Samping (Side Channel Spillway) Bendungan Beringin Sila Kabupaten Sumbawa - Aulia, Nanda; Dermawan, Very; Cahya, Evi nur (Fakultas Teknik, Universitas Brawijaya, 2021)
The construction of the Beringin Sila dam is a priority to provide irrigation water and meet raw water requirements in the Utan and Buer districts. To address this issue, the Beringin Sila Dam is one of the government's efforts to build equitable infrastructure to support national water and food safety. The hydraulic analysis of the physical design of the Beringin Sila dam is one of the planning rules for the dam. The goal of the analysis of the physical model of the Beringin Sila dam is to evaluate and propose the best alternative to improve the overall hydraulic performance based on initial planning. The hydraulic analysis of the physical model of the Beringin Sila dam was carried out with the initial planning of the series 0 using the standard stage method on the transition channel and the chute way. The physical model test results show that the design of the dam is safe to flow the Q100th and Q1000th discharge because the conditions of the transition channel are not crossflow, the chute way channel is supercritical and there is no capitation and vibration flow.